Generalized Modified Group Chain Sampling Plan based on Non-symmetrical Data - Nazrina Aziz; Abdur Razzaque Mughal; Zakiyah Zain; Nor Hisham Haron (International Journal of Supply Chain Management, 2017)
Acceptance sampling is a quality control technique widely used by companies in deciding whether or not to accept a lot or batch of products based on the inspection result of a sample taken from the lot. Majority of acceptance sampling plans are developed assuming symmetrical data distribution, whereas actual scenarios include product lifetime which is often non-symmetrical. In this article, a generalized modified group chain sampling plan (GMGChSP) based on non-symmetrical data is proposed using preceding lot information. An iterative technique is employed to find the design parameters of the proposed plan by satisfying the pre-specified consumers risks, number of testers and proportion defective. The performance of the proposed plan is compared to an established plan developed by Mughal et al. (2016b).